Economic Impact Comparison of the MBG Program on Students, Canteens, MSMEs Before–After - Septiana Dwi Nurmala; Fridhia Nabilla Zahra; Alia Putri Fadhilah; Dinda Juliana Putri; Margiyana Retno Wulan; Tiya Marshanda Fahmi (Pattimura Proceeding, 2026)
This study aims to compare the economic impact of the Free Nutritious Meal Program (MBG) on students, school canteens, and nearby MSMEs before and after the program’s implementation. The research was conducted at SMA Negeri 5 Bandar Lampung using a mixed-method approach, combining in-depth interviews with questionnaires distributed to students, canteen operators, and surrounding MSME owners. The findings show that the MBG program provides meaningful benefits to students by reducing their daily food expenses and improving access to nutritious meals, consistent with evidence indicating that MBG initiatives enhance students’ nutritional adequacy (Merlinda & Yusuf, 2025). However, the program also generates economic pressure on school vendors and local MSMEs, as reflected in studies reporting a decline in canteen income following the introduction of free meal policies (Ariska et al., 2025). This phenomenon aligns with the concept of crowding-out in food assistance interventions, wherein government-provided meals reduce consumer demand for existing food providers (Ruffini et al., 2023)These findings highlight the need for a more inclusive policy design, such as integrating local MSMEs into the MBG supply chain or establishing school–MSME partnerships to support economic sustainability without undermining the program’s primary goals.